Mapping of poverty and likely zoonoses hotspots - Grace, Delia; Mutua, Florence K.; Ochungo, P.; Kruska, Russell L.; Jones, K.; Brierley, L.; Lapar, Ma. Lucila; Said, Mohammed Yahya; Herrero, Mario; Phuc, P.M.; Thao, N.B.; Akuku, I.; et al. (International Livestock Research Institute, 2012)
The objective of this report is to present data and expert knowledge on poverty and zoonoses hotspots to inform prioritisation of study areas on the transmission of disease in emerging livestock systems in the developing world, where prevention of zoonotic disease might bring greatest benefit to poor people.